“When asked to join the partisan detachment, the district prosecutor, comrade Onushko, refused...” - V. A. Bondarev; Yu. A. Bulygin (Шаги)
The publication contains an analysis of an original archival document from the collections of the Center for Documentation of Contemporary History of the Rostov Region. The document, introduced into scholarly circulation for the first time, provides information about little-known and insufficiently studied aspects of the partisan movement in the USSR during the Great Patriotic War. This is a memorandum, “On the issue of relationships in the leadership of the Upper-Don district [Rostov Region]”, addressed to B. A. Dvinsky. the first secretary of the Rostov regional committee of the All-Union Communist Party(Bolsheviks) and compiled by the deputy secretary of the regional committee, Gorshkov, in early December 1943. The report describes in detail the acute interpersonal conflict that flared up within the leadership of the Upper-Don district of the Rostov region in August 1943. The root cause of the conflict was the reluctance of the district prosecutor, Onushko, to join the partisan detachment formed from local communists when Nazi troops approached the Upper-Don region in the summer of 1942. Onushko’s inappropriate behavior provoked criticism from other members of the district leadership, for which the prosecutor tried to take revenge using his official position. Thus, Gorshkov’s memo allows us to consider the partisan movement in the light of interpersonal relationships, which creates opportunities for a more in-depth study of the moods of Soviet partisans, their conflicts and contacts, everyday life, etc.